Analysis Of The Influence Of The Tourism Sector On Economic Growth In The Provinces Of Bali And West Nusa Tenggara - Wiwin Octavia Isroissholikhah; Sishadiyati, Sishadiyati (Cita konsultindo, 2024)
Economic growth is important for every country. A sign that things are improving in a region is good and increasing economic growth. An important part of any country's economy is the tourism industry. One of the main drivers of economic growth in Indonesia is the tourism industry. The tourism sector itself is the strongest and largest sector in Indonesia's economic development efforts compared to other sectors. This is because the tourism industry provides various types of services that can be offered such as the provision of hotels, restaurants, transportation, money changers, tour guides and others. The impact of tourism activities has a great influence on the community around the tourist destination area. The more tourism activities that occur in the area, the more regional income will come in. In addition, the more attractions that an area presents, the more tourists will visit the place. This study uses a quantitative method of multiple linear analysis with variables of the number of tourists, number of hotels, and number of tourist attractions in the provinces of Bali and West Nusa Tenggara in 2011-2021.